Pengaruh Ukuran Perusahaan, Profitabilitas dan Leverage terhadap Nilai Perusahaan pada Perusahaan Food and Beverages yang Terdaftar di BEI (Tahun 2019-2023) - Natalia Shinta Puspitasari; Dorothea Ririn Indriastuti (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
The trust of investors to invest their shares in a company is one of the strong spears for the survival of a company. Investors often look at the company's financial statement information as a consideration for decision making in investing their shares, whether the shares given to the company will produce or too many risks and losses. The purpose of this study was to determine the significance of the effect of company size, profitability and leverage on firm value. This type of research is a case study on food and beverage companies listed on the Indonesia Stock Exchange. The company population was 24 companies with a sample of 15 companies using purposive sampling technique. Data collection using documentation and literature study. The data analysis technique uses multiple linear regression methods, t test, F test and coefficient of determination. The results showed that company size has a significant effect on firm value with a negative regression coefficient value so that the higher the company size, the company value will decrease. Profitability (ROE) has a significant effect on firm value with a positive regression coefficient value, meaning that the better the company's profitability, the company's value will also increase. Leverage (DER) has no effect on firm value with a negative regression coefficient value so that the higher the leverage, the company value will decrease.